Hoarseness revealing Ortner's syndrome. Issue 3 (June 2015) - Verbeke, X.; Vliebergh, J.; Sauer, M.; Leys, M.
Abstract : Hoarseness is a common phenomenon that can be caused by uncommon pathology. One seldom cause is Ortner's syndrome, a rare cardiovocal disease that can lead to hoarseness due to left recurrent laryngeal nerve palsy induced by mechanical compression of the nerve by cardiovascular structures. This case report describes a case of a 41-year-old woman with sudden onset of hoarseness. The patient had known pulmonary hypertension and Eisenmenger's syndrome.